Man posing along a wall of paintings - Unknown:::Creator::::::::::::
Photograph shows a man in a suit and tie posing along a wall with his left hand on a painting. The wall has similar paintings exhibited along the length of it. Tags can be seen affixed on the bottom of three paintings.